2022
DOI: 10.22271/j.ento.2022.v10.i5c.9059
|View full text |Cite
|
Sign up to set email alerts
|

Pests and predators interference on the stingless bee population inhabited at different habitats amidst south-eastern Karnataka, India

Abstract: Stingless bees (Hymenoptera: Apidae: Meliponini) are called 'Dammar bees' live under cryptic conditions at diversified ecosystems. Stingless bees are one of the most important species, playing pivotal role as 'Keystone Pollinators' for various flowering plant species. Besides, they are cultured in the name of 'Meliponi culture' at various man-made agro-ecosystems. Reports on biological constraints of stingless bees is limited at south-eastern Karnataka, hence in the present study commonly occurring constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Solitary bees M. disjuncta and Megachile cephalotes were observed to rob the resin applied at the nest entrance. Gopinatha & Basavarajappa (2022) reported that M. disjuncta collects wax and cerumen, especially from pollen cells and brood cells in the nest of stingless bees. The allocation of tasks for colony defence might occur appropriately after substantial development of the colony with a sufficient number of foragers allotted as guard bees to defend against intruders.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary bees M. disjuncta and Megachile cephalotes were observed to rob the resin applied at the nest entrance. Gopinatha & Basavarajappa (2022) reported that M. disjuncta collects wax and cerumen, especially from pollen cells and brood cells in the nest of stingless bees. The allocation of tasks for colony defence might occur appropriately after substantial development of the colony with a sufficient number of foragers allotted as guard bees to defend against intruders.…”
Section: Discussionmentioning
confidence: 99%